2021
DOI: 10.7759/cureus.19787
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Informed Consent and the Impact of Simulation on Anesthesia Trainees

Abstract: Introduction Over the years, the process of obtaining informed consent has evolved and now places an emphasis on the concept that patients should play a major role in medical decision making. Failure to adequately involve patients in making decisions regarding their health can lead to medicolegal consequences. Therefore, taking informed consent is a fundamental component of anaesthesia training. Simulation, for training, is an excellent tool that is being utilised widely in the training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The study demonstrated that residents who received any type of training whether in the form of a video curriculum or through journal articles performed better on the postintervention objective structured clinical examination (OSCE) [16 & ]. In another study, anesthesiology trainees demonstrated an improvement in obtaining informed consent after simulation-based training [22]. Improvement in post intervention performance was observed in description of the procedure, discussion of alternatives, disclosure of associated procedure risks, teach back, and documentation of patient's verbal consent [22].…”
Section: Shared Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study demonstrated that residents who received any type of training whether in the form of a video curriculum or through journal articles performed better on the postintervention objective structured clinical examination (OSCE) [16 & ]. In another study, anesthesiology trainees demonstrated an improvement in obtaining informed consent after simulation-based training [22]. Improvement in post intervention performance was observed in description of the procedure, discussion of alternatives, disclosure of associated procedure risks, teach back, and documentation of patient's verbal consent [22].…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…In another study, anesthesiology trainees demonstrated an improvement in obtaining informed consent after simulation-based training [22]. Improvement in post intervention performance was observed in description of the procedure, discussion of alternatives, disclosure of associated procedure risks, teach back, and documentation of patient's verbal consent [22]. These findings underscore the importance of formal training in advance care planning for anesthesiology trainees.…”
Section: Shared Decision-makingmentioning
confidence: 99%
“…Training that incorporates simulated or standardized patients (SPs) is an effective way to provide continuing education training to professionals in a variety of clinical contexts [16][17][18]. Specifically, the use of role-plays with SPs in training can increase clinicians' confidence [19] and performance [20,21] in conducting informed consent discussions for clinical procedures. More recently, researchers have begun to employ role-plays in training programs for staff conducting informed consent for research [22][23][24].…”
Section: Introductionmentioning
confidence: 99%